An AIE active imidazole conjugated α-cyanostilbene based sensor for the selective and sensitive detection of picric acid in an aqueous medium - Selin Manoj Kumar; Sathiyanarayanan Kulathu Iyer (Sensors and Actuators Reports, 2023)
Due to increasing pollution threats, terrorism-sensitive rapid sensing of aromatic nitro explosives (picric acid) has gained predominant significance in environmental safety. Herein, imidazole-derived monofunctional fluorescent sensor 2-(4-aminophenyl)-3-(3-(4,5-diphenyl-1H-imidazol-2-yl)-2-hydroxyphenyl) acrylonitrile (ADHA) was successfully developed for the selective recognition of explosive picric acid. The D-π-A configuration of ADHA facilitates extraordinary photophysical properties with remarkable aggregation-induced emission (AIE). The detection process is induced by the photon-induced electron transfer (PET) and resonance energy transfer (RET) and results in the generation of ADHA+PA complex. The structural relationship and the photophysical properties of ADHA were extensively studied by DFT (Density Functional Theory) methods and spectroscopic analysis. It has been calculated that the detection limit of the formed complex is 6.26 nM. In addition, 1H NMR titrations DFT calculations, and HRMS analysis were performed to understand the detection mechanism better. Test strip-aided detection and invisible ink applications confirmed that ADHA is a versatile sensor for sensitively detecting picric acid without sophisticated instruments. In addition, ADHA was implemented to detect PA in real water samples with remarkable recovery.